2022
DOI: 10.3390/nu14112196
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine, Paraxanthine, Theophylline, and Theobromine Content in Human Milk

Abstract: This study aimed to assess the content of caffeine and its metabolites—paraxanthine, theophylline, and theobromine—in breast milk according to selected factors. Samples of human milk were collected from 100 women living in the east–northeast region of Poland. Information on the consumption of beverages and foods containing caffeine was collected using a 3 day food record. The determination of caffeine and its metabolite content was performed using liquid chromatography–mass spectrometry (LC–MS/MS). This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The higher caffeine concentration in milk from donors with higher bacterial counts might be related to the participant's behavioral patterns. Purkiewicz studied a detailed 3-day caffeine intake history and reported that higher reported caffeine intake corresponded to higher caffeine concentration in human milk (Purkiewicz et al, 2022). In contrast, Escuder-Vieco et al (2014) reported that a lifestyle questionnaire is reliable for the assessment of illicit drug use by donors to a human milk bank; however, there are certain limitations regarding the disclosure of the consumption of caffeinated beverages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher caffeine concentration in milk from donors with higher bacterial counts might be related to the participant's behavioral patterns. Purkiewicz studied a detailed 3-day caffeine intake history and reported that higher reported caffeine intake corresponded to higher caffeine concentration in human milk (Purkiewicz et al, 2022). In contrast, Escuder-Vieco et al (2014) reported that a lifestyle questionnaire is reliable for the assessment of illicit drug use by donors to a human milk bank; however, there are certain limitations regarding the disclosure of the consumption of caffeinated beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Donor registration is possible one month postpartum, and many donors are several months postpartum. A study of 100 lactating women in Poland reported higher caffeine concentrations during the later postpartum period (Purkiewicz et al, 2022). We believe that the donors in our study were more likely to have increased caffeine intake because of the number of postpartum days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mother's milk is considered the gold standard in infant nutrition; due to its unique composition that adapts individually to the needs of the child, it is highly recommended that babies be fed only the mother's milk until the child is at least 6 months old [1,2]. Such a position is recommended by, amongst others, the American Academy of Pediatricians (AAP) and the American Academy of Family Physicians (AAFP), who emphasize that breastfeeding reduces the risk of disease later in life [3].…”
Section: Introductionmentioning
confidence: 99%